THE ROLE OF THE FAMILY IN CHARACTER EDUCATION FOR CHILDREN - Mustafa Habib; Dina Nadira (PT Rahis Cendekia Indonesia, 2024)
Family is not only a place where father, mother and children gather. A real family is more than that. Family is the most comfortable place for children. A happy family is like heaven on earth, as the words of the Prophet Muhammad SAW, that